2011
DOI: 10.1016/j.suponc.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III Randomized, Double-Blind, Placebo-Controlled Study of Pilocarpine for Vaginal Dryness: North Central Cancer Treatment Group Study N04CA

Abstract: Purpose Vaginal dryness is a common problem, for which effective and safe non-estrogenic treatments are needed. Based on preliminary promising data that pilocarpine attenuated vaginal dryness, the current trial was conducted. Methods A double-blind, placebo-controlled, randomized trial design was used to compare pilocarpine, at target doses of 5 mg twice daily and 5 mg four times daily, to a placebo. Vaginal dryness was recorded by patient-completed questionnaires at baseline and weekly for 6 weeks after stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A total of 55 studies were deemed eligible for inclusion ( Table 1, Supplementary material ). The approaches tested to treat vaginal atrophy and sexual dysfunction were as follows: lubricants and moisturizers (18 studies, 14 15 16 17 18 19 20 21 22 23 24 25 26 5 27 28 29 30 31 of which evaluated hyaluronic acid); phytoestrogens (14 studies); 30 32 33 34 35 36 37 38 39 40 41 42 43 44 dehydroepiandrosterone (DHEA; 8 studies); 27 45 46 47 48 49 50 51 ospemifene (5 studies); 52 53 54 55 56 vaginal testosterone (4 studies); 16 19 57 58 pelvic floor muscle exercises (2 studies); 59 60 oxytocin (2 studies); 61 62 vaginal CO 2 laser (2 studies); 63 64 lidocaine (1 study);…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 55 studies were deemed eligible for inclusion ( Table 1, Supplementary material ). The approaches tested to treat vaginal atrophy and sexual dysfunction were as follows: lubricants and moisturizers (18 studies, 14 15 16 17 18 19 20 21 22 23 24 25 26 5 27 28 29 30 31 of which evaluated hyaluronic acid); phytoestrogens (14 studies); 30 32 33 34 35 36 37 38 39 40 41 42 43 44 dehydroepiandrosterone (DHEA; 8 studies); 27 45 46 47 48 49 50 51 ospemifene (5 studies); 52 53 54 55 56 vaginal testosterone (4 studies); 16 19 57 58 pelvic floor muscle exercises (2 studies); 59 60 oxytocin (2 studies); 61 62 vaginal CO 2 laser (2 studies); 63 64 lidocaine (1 study);…”
Section: Resultsmentioning
confidence: 99%
“…Regarding side effects, the results for lubricants and moisturizers indicated that all adverse events (AEs) were considered mild in severity and self-limited. 14 15 16 17 18 19 20 21 22 23 24 25 26 The most common AEs were burn on the application site, discomfort on the application site, vulvovaginal pruritus, and general pruritus. The compound hyaluronic acid has been shown to be well tolerated without side effects among most patients tested.…”
Section: Resultsmentioning
confidence: 99%
“…The authors did not find improvements invaginal dryness compared with placebo. Thus, pilocarpine cannot be recommended for use in the treatment of vaginal dryness, despite the preliminary pilot information that suggested that it might have been beneficial[ 211 ].…”
Section: Current Treatment Options For Genitourinary Syndrome Of Meno...mentioning
confidence: 99%
“…Pilocarpine (+)-1 ( Figure 1 ) is the main alkaloid of the South American tree Pilocarpus jaborandi , and it is usually isolated from its leaves. Pilocarpine is used as a cholinergic [ 1 , 2 , 3 ] parasympathomimetic [ 4 , 5 , 6 , 7 , 8 ], hidrotic and miotic agent [ 9 , 10 ]; in ophthalmology, it is used against glaucoma [ 11 , 12 , 13 ] and also acts as an antagonist [ 14 , 15 , 16 ] to atropine and as an inhibitor of the enzyme carbonic anhydrase II [ 17 , 18 , 19 ]. Moreover, a deficiency of carbonic anhydrase in humans is linked to osteopetrosis; thereby, osteoclasts are unable to perform bone resorption in a normal way [ 20 ].…”
Section: Introductionmentioning
confidence: 99%